Verifying temporal data in geotagged images via sun Azimuth estimation - Sudha, N. (2012)
Image metadata provides useful information for applications such as image retrieval, content description and geolocation. However, it is relatively easy to tamper with this data using metadata manipulation tools. In this paper, we address the issue of authenticating the time of capture of an image based on its geolocation information. By utilizing a novel two-stage shadow detection process, we are able to estimate the azimuthal direction of the sun in an image and compare it against a calculated theoretical value to establish the authenticity of the time of capture. In case of ambiguous direction estimation from shadows, we improve an existing method using cues from vertical surfaces to resolve the ambiguity. The sky is used as a cue to perform verification in difficult scenarios such as the absence of shadows. Results are provided which show that our technique is able to estimate the sun azimuth with good accuracy. Additional results pertaining to date verification and camera direction estimation are also provided.